Implant restorations : a step by step guide - Drago, Carl J. (Ames, Iowa : Blackwell, 2014)
Implant Restorations: A Step-by-Step Guide, Third Edition offers clinicians a practical, step-by-step approach to treatment planning and restoring dental implants. This highly illustrated, case-based book demonstrates how to treat the most commonly encountered treatment scenarios, describing the procedures, techniques, and sequences required in clear, concise language and in an easy-to-use format. The book takes the theory of implant restoration, using as its basis 3i's implant systems, and places it directly in the operatory, concentrating in detail on each stage of the actual clinical proce.
Introduction to implant dentistry -- Implants and implant restorative components -- Diagnosis and treatment planning in implant restorative dentistry -- Treatment of a patient with an edentulous mandible-implant retained bar overdenture and resilient attachments -- Treatment of a patient with a partially edentulous mandible using intra-oral scanning (IOS) of a CADCAM healing abutment -- Re-treatment of a patient with a fractured implant-retained fixed partial denture in the posterior maxilla-CAD/CAM abutments and a new fixed partial -- Accelerated treatment protocol of a patient with edentulous jaws and CAD/CAM titanium framework/fixed hybrid prostheses -- Treatment of a patient with an edentulous mandible with an immediate occlusal loading protocol (DIEM2) -- Treatment of an edentulous patient with an accelerated treatment protocol and immediate occlusal loading protocol (All on 4) -- Immediate non-occlusal loading provisional restoration; intra-oral scanning, CAD/CAM abutment and definitive restoration maxillary central incisor -- Computed tomography (CT) guided surgery/immediate occlusal loading with a full arch prosthesis in the edentulous mandible -- Review of concepts for designing and fabricating metal implant frameworks for hybrid implant prostheses.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dental implants; MEDICAL -- Surgery -- General; Dental implants; Dental Implantation, Endosseous -- methods; Dental Abutments; Jaw, Edentulous -- surgery; Electronic books; Electronic books